Impulso Historiográfico na prática artística de Rosana Paulino: o caso da exposição Atlântico Vermelho no Padrão dos Descobrimentos (2017) - Vasconcellos, Lucas Ferreira de; Rita Lages (Farol, 2021)
This paper critically analyzes the exhibition Atlântico Vermelho, by the artist Rosana Paulino, held between october and december 2017, at Padrão dos Descobrimentos, a monument located in Lisbon, Portugal. Therefore, the concept of Historiographical Impulse, presented by Giselle Beiguelman (2019), is taken as a notion of artistic practice that questions and reissues as absolute truths in institutional circuits and in the monumentalization of history. This concept must be worked on processes of cultural heritage properties (re) interpretation, especially historical monuments, on which artist Rosana Paulino works. Decolonial feminist criticism is used as a critical basis.